A successful management of left-sided posterior congenital diaphragmatic hernia of the jejunum, ileum, colon and left kidney: a case report. Issue 11 (19th November 2022) - Al-Abdullah, Zainab; Duvuru, Ruthwik; Nawaz, Faisal A; Ennab, Farah; Alklani, Temaa; Ahmed, Aftab
Abstract: Congenital diaphragmatic hernia (CDH) is a rare developmental anomaly in which abdominal contents herniate into the thoracic cavity due to underdevelopment of the diaphragm, possibly leading to pulmonary hypoplasia. Whereas surgery is not the first priority in treatment, it must be performed within a window of 2 weeks and after hemodynamic stability has been achieved. The patient described in this case report had a CDH of the jejunum, ileum, colon and left kidney diagnosed in a boy of South Asian origin who presented with tachypnea in the third hour of life. Imaging studies conducted included chest X-ray, chest ultrasound including echocardiogram, and abdominal and pelvic ultrasound. Treatment and management were successful despite complications. Future research on CDH is warranted in the populations in the Middle East, and local guidelines must be generated in order to improve diagnosis, treatment and prognosis.